An Analysis of Visitor Perception Toward Shariah-Compliant Hotels in Contemporary Hospitality - Singgalen, Yerik Afrianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research examines visitor perceptions of Shariah-compliant hotels within the context of contemporary hospitality, focusing on how these establishments meet guest expectations and foster satisfaction in a competitive global market. The study analyzes 445 customer reviews using a descriptive-analytical methodology to explore integrating Islamic principles with modern service standards. Key themes include cleanliness, staff behavior, Halal compliance, and family-oriented facilities. Cleanliness, mentioned in over 30% of reviews, emerges as the most critical factor, reflecting its alignment with Islamic values and universal hospitality standards. Staff behavior, noted in 25% of reviews, highlights the importance of attentiveness and politeness in shaping guest perceptions. Halal compliance, cited in 20% of feedback, underscores the significance of providing prayer facilities and Halal-certified dining options for Muslim travelers. Family-friendly and worship-related amenities, accounting for 15% of mentions, illustrate the need for culturally and spiritually inclusive environments. Sentiment analysis reveals a weak positive correlation (0.165) between ratings and sentiment polarity, while dissatisfaction, noted in 10% of reviews, primarily relates to tranquility, maintenance, and service inconsistencies. The findings emphasize that the success of Shariah-compliant hotels relies on the seamless integration of faith-based principles with operational excellence. Addressing guest concerns and leveraging positive feedback enhances satisfaction and strengthens loyalty and competitiveness. This study contributes to the broader discourse on inclusive hospitality management, offering practical insights for operational improvement and theoretical advancements in understanding niche markets.